2014
DOI: 10.1264/jsme2.me13160
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite-Primed PCR for Intra-species Genetic Relatedness in <i>Trichophyton ajelloi</i> Strains Isolated in Poland from Various Soil Samples

Abstract: Trichophyton ajelloi is a geophilic dermatophyte that specializes in the decomposition of native keratin. It exists in soil with a permanent influx of keratin matter. In the present study, two PCR-based methods were used for the identification and intra-species differentiation of T. ajelloi strains isolated from 3 types of soils with different physicochemical properties. The first method, employed for molecular identification, was PCR amplification of the 5.8S rRNA gene and its flanking regions encoding intern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…While A. uncinatum is also a geophilic species known to be most frequently isolated from humus-rich soils, the infrequency of this species in the current survey can be attributed to the low degree of acidity in most soils samples from Iran (pH ≥ 7). Statistically substantiated studies from Europe [ 21 , 22 , 24 , 25 ] have reported that A. uncinatum in an exceptionally acidophilic species that is less-abundantly isolated from soils with pH > 6.0. In different inquiries from Iran [ 10 , 12 , 14 ], Tunisia [ 29 ] India [ 1 , 2 , 30 ], Saudi Arabia [ 7 ], the USA [ 18 ] and Brazil [ 27 ], the dermatophytes were isolated from a wide variety of soils, especially from shady and wet places rich in organic substances, e.g., gardens, public grasslands, sludge and cultivated fields, or locations with a high animal keratin content.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…While A. uncinatum is also a geophilic species known to be most frequently isolated from humus-rich soils, the infrequency of this species in the current survey can be attributed to the low degree of acidity in most soils samples from Iran (pH ≥ 7). Statistically substantiated studies from Europe [ 21 , 22 , 24 , 25 ] have reported that A. uncinatum in an exceptionally acidophilic species that is less-abundantly isolated from soils with pH > 6.0. In different inquiries from Iran [ 10 , 12 , 14 ], Tunisia [ 29 ] India [ 1 , 2 , 30 ], Saudi Arabia [ 7 ], the USA [ 18 ] and Brazil [ 27 ], the dermatophytes were isolated from a wide variety of soils, especially from shady and wet places rich in organic substances, e.g., gardens, public grasslands, sludge and cultivated fields, or locations with a high animal keratin content.…”
Section: Discussionmentioning
confidence: 89%
“…While members of the N. gypsea complex were the dominant species in the soils from different localities in Iran, species other than this complex were more distinguished in the soils from some European countries. In five different reports from 1992 to 2013, T. ajelloi (currently, A. uncinatum ) was the most commonly isolated species from soils in Italy, Poland, Austria and Slovakia [ 21 , 22 , 23 , 24 , 25 ]. Such differences in species domination can be justified with differences in the types of soils sampled.…”
Section: Discussionmentioning
confidence: 99%
“…One of the more common soil keratinomycetes is Trichophyton ajelloi , which belongs to geophilic dermatophytes [ 24 , 25 , 26 , 29 ]. There is little data in the literature comprehensively describing keratin breakdown by these fungi [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Infected animals sometimes act as vectors to transmit zoophilic fungi to human hosts, which mostly lead to acute, highly inflammatory mycoses. Geophilic fungi reside in soil around the burrows of specific terrestrial mammals 3,4 . Geophilic fungi are regarded as ecological ancestors of anthropophilic fungi, which correspond with molecular phylogeny.…”
Section: Introductionmentioning
confidence: 99%
“…Geophilic fungi reside in soil around the burrows of specific terrestrial mammals. 3,4 Geophilic fungi are regarded as ecological ancestors of anthropophilic fungi, which correspond with molecular phylogeny. According to the new taxonomy, dermatophyte species are grouped into seven genera: Trichophyton, Epidermophyton, Nannizzia, Paraphyton, Lophophyton, Microsporum and Arthroderma.…”
Section: Introductionmentioning
confidence: 99%